Effectiveness Of Task Instruction Sheet Strategy In Enhancing Pupils’ Interest and Performance in Some Difficult Basic Science and Technology Concepts under Covid-19 Preventive Protocol - Dawal, Blessing Solomon (NIU Journal of Humanities, 2021)
The study sought to find out the effectiveness of task instruction sheet strategy in enhancing pupils interest and performance in some difficult basic science and technology concepts under covid-19 preventive protocol. Two research questions and two hypotheses were formulated to guide the study. The non-equivalent quasi experimental research design was adopted. The sample consisted of 178(92 boys and 86 girls) primary six pupils drawn through simple random, sampling technique from 21 public primary schools in Jos North West of Plateau State. The instrument for collecting the data was a valid 20 item interest inventors and 25 item multiple choice performance test with relativity indices of 0.78 and 0.84 respectively. The experimental and control groups were taught the difficult concepts for 8 weeks using task instruction sheet strategy and conventional lecture methods respectively. The data collected were analyzed using mean and standard deviation for research questions and analysis of covariance for the hypotheses at 0.05 level of significance. The result of the study revealed that task instruction sheet strategy enhanced pupilsâ€™ interest and performance in basic science and technology than the conventional lecture method. The experimental group developed significantly higher interest in the difficult concepts thereby performing better than the control group. It was recommended among others that teachers adopt the task instruction sheet strategy in teaching especially when dealing with difficult basic science and technology concepts.  Keywords: Interest, Performance, difficult concepts, task instruction sheet strategy, and Covid19 Prevention Protocol.